Biogenesis of Circular RNAs. - Vicens, Q.; Westhof, E. (Cell, 2014)
Circular RNAs are generated during splicing through various mechanisms. Ashwal-Fluss et al. demonstrate that exon circularization and linear splicing compete with each other in a tissue-specific fashion, and Zhang et al. show that exon circularization depends on flanking intronic complementary sequences. Both papers show that several types of circular RNA transcripts can be produced from a single gene.